If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2 = 5y + 7 Reorder the terms: 2 + 2x = 5y + 7 Reorder the terms: 2 + 2x = 7 + 5y Solving 2 + 2x = 7 + 5y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2x = 7 + -2 + 5y Combine like terms: 2 + -2 = 0 0 + 2x = 7 + -2 + 5y 2x = 7 + -2 + 5y Combine like terms: 7 + -2 = 5 2x = 5 + 5y Divide each side by '2'. x = 2.5 + 2.5y Simplifying x = 2.5 + 2.5y
| 9M^2+12M-12=0 | | 6x^3-6x^2-6x=o | | 4x-4=6x-6 | | 1/3x-1/2+5/5x=3 | | 80=2lw+2lh+2wh | | (X+2)(X+3)=(X-4)(X-5) | | 6x+3x=5-4(2x-3) | | (8/2x+2)=(3/x-1) | | 2x+13=-35 | | -x/7=12 | | 94-3x=11-8x | | x=33800/1.04 | | -7/3a=35 | | 93-3x=11-8x | | (9X-2)-(X+3)=(X-5)(X-7) | | 15x^3-42x^2=0 | | -3+10x+4x^2=0 | | 4x+39=10x-45 | | 3/2x-2/3=13 | | 4/10=2x/x+6 | | 0.05(3t+7)=0.15(t-4)+0.95 | | x-2(x+1)=7-4x | | 120=120 | | Y=2.50+0.05*x | | 1+15x+20=5(3x+4) | | -5+2x+x^2=0 | | 3(x+3)+5=6x-3(-3+x) | | ((1/2)-(2/3x))/((1/x)+(1/6)) | | 8m-11=16 | | x/3+2=x/5+4 | | 4v^2-13v+10=0 | | 2(2n+2)=6(8n+3)+3 |